Manuka honey in combination with 5-Fluorouracil decreases physical parameters of colonspheres enriched with cancer stem-like cells and reduces their resistance to apoptosis. (16th April 2022) - Cianciosi, Danila; Forbes-Hernández, Tamara Y.; Regolo, Lucia; Alvarez-Suarez, José M.; Quinzi, Denise; Sargenti, Azzurra; Bai, Weibin; Tian, Lingmin; Giampieri, Francesca; Battino, Maurizio
Highlights: Manuka honey with 5-Fluorouracil decreases physical parameters of colonspheres. Manuka honey with 5-Fluorouracil reduces apoptosis rate of cancer stem-like cells. Manuka honey with 5-Fluorouracil downregulates many apoptotic inhibitors. Manuka honey and 5-Fluorouracil reduce spheroid mass density, weight and diameter. Manuka honey and 5-Fluorouracil increase the apoptotic cells number in colonspheres. Manuka honey and 5-Fluorouracil increase the number of dead cells in colonspheres. Manuka honey and 5-Fluorouracil downregulate many apoptotic inhibitors. Abstract: The aim of the present work was to evaluate the in vitro effect of Manuka honey and its combination with 5-Fu, the most common drug used in the treatment of colon cancer, on the morphological and physical parameters of colonspheres enriched with cancer stem-like cells deriving from HCT-116 colon adenocarcinoma cell line and on the apoptosis rate. Manuka honey, alone and more in combination with 5-Fu, reduced the weight, the diameter and mass density of the spheroids and induced apoptosis through the downregulation of many apoptosis inhibitors, including IAPs (Livin, Survivin, XIAP), IGFs (IGF-I, IGF-II and IGF-IR) and HSPs (HSP-27, HSP-60 and HSP-70). These results led to a reduction in the survival ability of cancer stem-like cells, as well as to a chemosensitizing effect of honey towards 5-Fu, considering that apoptosis resistance is one of the main causes of cancer stem-like cells chemoresistance.